2022
DOI: 10.1021/acschembio.2c00405
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Protein Import into the Endoplasmic Reticulum in Living Cells with Proximity Labeling

Abstract: The proper trafficking of eukaryotic proteins is essential to cellular function. Genetic, environmental, and other stresses can induce protein mistargeting and, in turn, threaten cellular protein homeostasis. Current methods for measuring protein mistargeting are difficult to translate to living cells, and thus the role of cellular signaling networks in stress-dependent protein mistargeting processes, such as ER pre-emptive quality control (ER pQC), is difficult to parse. Herein, we use genetically encoded per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…We also compared the effect of Hspa13 overexpression to UPR induction by thapsigargin (Tg), which promotes secretion of aggregation-prone conformations of TTR ( 79 ). While Tg upregulates the UPR target BiP, and modestly inhibits TTR import efficiency ( 44 , 46 ), it does not increase insoluble TTR to a similar extent as Hspa13 overexpression does ( Fig. S4 D ).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…We also compared the effect of Hspa13 overexpression to UPR induction by thapsigargin (Tg), which promotes secretion of aggregation-prone conformations of TTR ( 79 ). While Tg upregulates the UPR target BiP, and modestly inhibits TTR import efficiency ( 44 , 46 ), it does not increase insoluble TTR to a similar extent as Hspa13 overexpression does ( Fig. S4 D ).…”
Section: Resultsmentioning
confidence: 95%
“…Another possibility is that Hspa13 inhibits signal peptide cleavage directly, with immature Flag TTR then being rapidly retrotranslocated to the cytosol through ERAD. However, we have previously demonstrated that the inhibition of TTR signal peptide cleavage in the ER does not induce its cytosolic accumulation ( 46 ) but rather leads to ER accumulation of immature TTR instead.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations